2004
DOI: 10.3171/jns.2004.101.5.0878
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of pseudotumor cerebri after bariatric surgery for related obesity

Abstract: Two obese women, both of whom were 42 years of age, were examined for pseudotumor cerebri. Intracranial venography revealed increased pressure in the dural venous sinuses and the right atrium. The increased right atrial pressure was attributable to the patients' obesity. Both patients underwent bariatric surgery to achieve weight loss. Approximately 1 year later, a clinical evaluation showed that in both women the pseudotumor cerebri had resolved. Repeated measurements of dural venous pressure indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 7 publications
0
57
0
Order By: Relevance
“…Another case report demonstrated a reduction of dural venous sinus pressure in 2 patients following bariatric surgery. 46,47 Medications to treat and prevent recurrence of PTC typi- cally have activity against carbonic anhydrase, which has been found to decrease the rate of CSF production, and thus address 1 of the proposed mechanisms of PTC. 22 Acetazolamide is historically the most commonly used medication to treat PTC, but topiramate has been shown to have equal effect as a result of partial carbonic anhydraseϪinhibition activity augmented by beneficial analgesic action against headaches and weight loss as a fortuitous side effect.…”
mentioning
confidence: 99%
“…Another case report demonstrated a reduction of dural venous sinus pressure in 2 patients following bariatric surgery. 46,47 Medications to treat and prevent recurrence of PTC typi- cally have activity against carbonic anhydrase, which has been found to decrease the rate of CSF production, and thus address 1 of the proposed mechanisms of PTC. 22 Acetazolamide is historically the most commonly used medication to treat PTC, but topiramate has been shown to have equal effect as a result of partial carbonic anhydraseϪinhibition activity augmented by beneficial analgesic action against headaches and weight loss as a fortuitous side effect.…”
mentioning
confidence: 99%
“…This is reflected in our cohort of patients, all of whom are female with an average age of 32 and mean body mass index of 46.05 kg/m 2 at initial presentation. IIH is a poorly understood entity, with several postulated causes or predisposing factor [7][8][9][10]. All patients in our cohort had been investigated and When considered as a whole, our group of patients had suffered with a rather refractory form of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nadkarni et al have stated that the increased intracranial pressure is caused by high right atrial pressure, which itself is a direct result of obesity [7]. This has complemented other such work which has identified intra-abdominal pressure increases in obesity as the primary contributory factor in IHH [8,9].…”
Section: Introductionmentioning
confidence: 93%
“…The first case was reported by Fontes et al, 21 who observed that complete resolution of PC-related symptoms was achieved in a 37-yearold female after RYGB. Nadkarni et al 20 reported on two cases of obese women, both aged 42 years, who underwent gastric bypass and gastric stapling. Complete resolution of PC was observed at the one-year reevaluation.…”
Section: Case Reportmentioning
confidence: 99%